Alibaba’s growth frenzy : pioneer in China’s internet financial service - Hou, Shiyu; Wei, W. (Bill); Yue, Tao (London : Rotterdam School of Management, Erasmus University, 2024)
Alibaba has been heavily involved in financial innovations in China, offering services such as online payment, online retail wealth management and purely online insurance through its daughter companies Alipay, Ant Financial, and others. Internet-driven finance innovation is a driving trend in China, as opposed to countries such as the USA and the UK where the likes of Google and Facebook are dominant Internet companies but are not heavily involved in internet-driven finance. Considering that the financial sector is highly regulated in China, Alibaba’s role is ironic and heroic at the same time. Why are Alibaba’s Internet financial services innovative? What managerial challenges are there for an e-commerce company to run financial service? And what regulatory challenges are facing Alibaba? Who are competitors for Alibaba in this sector? What is the impact of Alibaba’s financial innovation on China’s financial system? How does big data analytics facilitate financial services? The case shows how an emerging Chinese Internet giant transforms from an e-commerce player to a significant financial service provider. It presents the managerial and regulatory challenges Alibaba encounters in this transformation and showcases its success in China’s reforming financial sector.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business -- Technological innovations -- China -- Case studies; Financial engineering -- China -- Case studies; Insurance -- China -- Case studies